Job Ladders by Firm Wage and Productivity - Antoine Bertheau; Rune Majlund Vejlin (Institute of Labor Economics (IZA), 2023)
We investigate whether workers reallocate up firm productivity and wage job ladders, and the cyclicality of this process. We document that productivity is a better measure of the job ladder than the average wage, since high productivity firms relative to low poach more workers than high wage firms relative to low. Employment cyclicality over the business cycle differs between the firm wage and productivity ladders. In recessions, employment decreases more in low than in high productivity firms. Low productivity firms fire more workers in recessions and stop hiring unemployed workers. Thus, there is a cleansing effect of recessions from the point of view of productivity reallocation. Oppositely, employment decreases more in high than in low wage firms, and the poaching channel of employment growth explains the difference. In recessions separations to other firms slow down more in low wage firms relative high wage firms and thus reallocation up the wage job ladder breaks down - a sullying effect of recessions. Thus recessions speed up productivity-enhancing reallocation but impede progression on the wage ladder.
Keywords: E24; E32; 330; job creation rate; firm heterogeneity; employment fluctuations